Discovering Halal Tourism’s Footprints: A Bibliometric Perspective On Business Research Using Scopus Data (1997–2023) - Ghifari Yuristiadhi M. Makhasi; Nur Syamsu; Muthmainnah MD; Sitti Aisya; Hariyanto Hariyanto (Universiti Sains Islam Malaysia, 2026)
Indexed by Scopus